CHEMICAL AND NUTRITIONAL STUDY OF ANDEAN GRAINS GERMINATED OF QUINOA (CHENOPOD/UM QUINOA) ANO AMARANTH (AMARANTUS CAUDATUS) - Bravo, M. (2013)
The germination process was applied to Andean grains: quinoa and amaranth, in arder to generate them physical and chemical changes, which are favorable for preparations less viscous and more energy, and increase nutrients. We worked with White quinoa and amaranth variety Junín Osear Blanco from Huancayo. The germination of the grains was higher in quinoa, amaranth not in yielding 98% and 70% germination respectively. The results Andes sprouted grains were: 13,09% protein, 6,10% fa!, 1,50% ash and 2,68% total fiber on a dry basis; vitamins 4,24 mg of niacin and 6,20 mg% ascorbic acid, minerals: 4,56 mg% iron, calcium 405,44 mg% and 39,86 mg% phosphorus for quinoa and 16,45% protein, 8,29% fat, 3,18% ash and 9,50% total fiber on a dry basis; vitamins 4,24 mg% niacin and 7,17 mg% ascorbic acid, minerals: 7,74 mg% iron,calcium 346,8 mg% and 49,0 mg% phosphorus for amaranth. The analyzes were períormed according to the AOAC methods.